PENGARUH DEBT TO EQUITY RATIO, CURRENT RATIO, NET PROFIT MARGIN TERHADAP DIVIDEN PAYOUT RATIO PADA SEKTOR PERDAGANGAN, JASA DAN INVESTASI - Tampubolon, Lasmaria; Marina, Marina; Hasrat, Hasrat (Aksara Public, 2019)
This study aims to determine the affect of the debt to equity ratio, current ratio and net profit margin to the ratio of dividend payments in the trade, services and investment sectors borh partial and simultaneous listed on the Indonesian stock exchange in 2013-2017. Research methods are carried aout with quantitative methods. Classid assumption test., multiple linear regression test and hypothesis test. Testing this study using version 20 of SPSS windows. The sample collection technique uses purposive sampling and the results af the study show that patially the debt to equity ratio has an effect on dividend payout ratio, the value with a significant t-count of 0,005 is smaller tham 0,05. current ratio does not effect on dividend payout ratio, the value with a significant t-count of 0,730 greater tham 0,05. Net profit margin does not effect on dividend payout ratio, the value with a significant t-count of 0,304 greater tham 0,05. While simultaneously the debt to equity ratio has an effect on dividend payout ratio, the value with a significant t-count of 0,038 is smaller tham 0,0.